A FAVELA EM PERSPECTIVA COMPARADA: A expressão do espaço nas obras Quarto de despejo de Carolina Maria de Jesus e Becos da Memória de Conceição Evaristo - SOUZA, Francisca Katrine de Carvalho (2023)
This dissertation aims to compare the ways of representing space and place in the works Quarto de despejo (1963) by Carolina Maria de Jesus and Becos da memória (2017) by Conceição Evaristo. Specifically, we intend to understand what role the slum plays both in the literary works in question, and in the very lives of these black women writers, trying to shed light on some structural links of their narrative constructions. Added to this is the even more complex issue of the place that Afro-Brazilian women's writing holds in the Brazilian literary space. Last, and not least, the exploration of the forms of symbolic definition of space and place verbalized by socially excluded subjects can be taken as an important laboratory for understanding everyday life and society. Objectively, while Carolina tells in this kind of diary her routine in the shantytown, how her life was and the daily struggles against hunger and misery living in a place of exclusion, in Becos da Memória, Conceição Evaristo tells how the shantytown was built, the arrival of the first residents and, finally, narrates its deconstruction with the demolition process, highlighting the fear and uncertainty in people's lives as they seek to rebuild their lives in a new place. Thus, by placing side by side biographical and literary experiences that hold familiarities, we seek to problematize the very tensions and challenges specific to literary creation. By virtue of the analytical challenges implied, on the other hand, the conceptual and methodological bases of the present research could only rest on an interdisciplinary reading grid, encompassing from the limits and possibilities of literary comparison, to even reflections on space and literature and black female protagonism in literature (CARVALHAL, 2006; NITRINI, 2010; TUAN, 1983; ASSMAN, 2011; SANTOS, 2009; DALCASTAGNÉ, 2014; CUTI, 2009; DUARTE 2018, among others). The results point to differences and similarities in the representativeness of the favela space in the referred works and its influence on the lives of the characters.